Creating a Handbook to Describe Employee Benefits for PT. WY’s New Employees - Florensia Nadya Lovillea (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
PT. WY is a manufacturing company which produces household and personal care products. Their main target market is family. The main problem is that new employees have no idea what to expect from this company, since there is no written information about employee benefits. Based on interviews and surveys, most employees did not know about the employee benefits of PT. WY, and the HRD representatives also agreed that they often asked about it. PT. WY actually has the handout, however, it is not complete yet, so they did not use it. Therefore, the solution is a handbook to describe employee benefits for the new employees. This project is done after reviewing theories by Bloomfield, Schofield, and Cantesbury (2015) and Martocchio (2016) and information from the company. This handbook is expected to help the company and its employees to always refer every information to the handbook. Keywords: employee, benefits, handbook